The excavation of an Early Bronze Age burnt mound at Arisaig, Lochaber, Highland (Scottish Historical and Archaeological Internet Reports, 2009)
During the upgrading of the A830(T), the 'Road to the Isles', the remains of a disturbed burnt mound deposit were discovered and later excavated during September and October 2005 by CFA Archaeology Ltd. This is the first such feature to have been excavated in this part of the Highlands. The burnt mound was discovered lying partly below a modern field bank on the edge of Arisaig (NGR: NM 6667 8650) during a trial trenching evaluation. Excavation demonstrated that the feature was formed in an active fluvial environment and that, despite the rural and boggy location, it had suffered considerable damage since its formation, caused by both the fluvial action of the adjacent stream and by a field drain. No evidence was found for either a hearth or a formal trough. The implication of a small assemblage of local quartz from within the burnt material is discussed. The charcoal assemblage is compared to spectra of pollen from contemporary deposits of peat in the area. Studies of the nature and origin of the burnt material via the results of soil magnetic susceptibility and thin-section analyses are presented. Six radiocarbon dates from three associated contexts span the period from 2550 to 1900 BC and suggest the burnt mound accumulated during the Early Bronze Age.